Effect of a High Protein, Low Glycemic Index Dietary Intervention on Metabolic Dysfunction-Associated Fatty Liver Disease: A Randomized Controlled Trial - Sun, Ping; Huang, Liping; Shuai, Ping; Wan, Zhengwei; Liu, Yingying; Xue, Jianqiang; Liu, Yuping (Frontiers in Nutrition, 2022)
Background: Metabolic dysfunction-associated fatty liver disease (MAFLD) is affecting people at an increasingly younger age. The primary treatment for patients with MAFLD is diet-induced weight loss; however, excessive dieting is poorly effective. Objectives: The aim of this trial was to evaluate if a high protein and low glycemic index (HPLG) dietary intervention would result in improvement of controlled attenuation parameter (CAP) and related metabolic markers in MAFLD. Methods: A 12-week controlled, parallel-group, randomized intervention trial was performed. Sixty-three participants with MAFLD were enrolled and randomized between the HPLG dietary group and the balanced diet control group. Both diets had the same hypocaloric level and were prescribed ad libitum within food limit lists. The primary outcome was CAP. The main secondary outcomes were weight loss and improvement of metabolism-related indexes at week 12 after program initiation. Results: A total of 59 participants completed the intervention and were included in the final analysis. The mean age was 39.3±8.9 years and 66.1% were male. In this trial, protein and carbohydrate intakes were significantly higher and lower, respectively, in the HPLG group compared to controls (P<0.001). At week 12, CAP was significantly reduced in both groups (P<0.001). However, a significantly greater reduction in liver fat was observed in the HPLG group compared to the control group (P=0.011), with mean relative reductions of 30.90dB/m (95%CI, 21.53 to 40.26, P<0.001) and 15.43dB/m (95%CI, 7.57 to 23.30, P<0.001) respectively. From baseline to week 12, a significantly greater loss in bodyweight was recorded in participants in the HPLG group (6.52kg; 95%CI, 5.50 to 7.54, P<0.001) compared to control subjects (2.00kg; 95%CI, 0.89 to 3.11, P=0.001). Moreover, body fat percentage in the HPLG group was significantly reduced compared with the control group (P=0.002). Within-group improvements in visceral fat, blood pressure, cardiovascular risk factors, and blood glucose-related indicators were detected in MAFLD patients assigned to the HPLG diet (P<0.05), but not in those prescribed the control diet (P>0.05). Conclusion: Under our experimental conditions, and compared to the traditional balanced diet, an HPLG diet led to significant CAP remission, bodyweight/fat reduction, and improvement of metabolic markers in MAFLD patients.